Expanding Philippine Trade: Measures to match Intra-ASEAN-4’s Trade Level - Anne Beatrice Concio; Geoffrey Federic Garcia; Vance Sañosa; Marie Antoinette Rosete (UJoST- Universal Journal of Science and Technology, 2022)
The Philippines has copious natural resources and a literate workforce, creating a possibility of further growth and being at par with Members’ Intra-ASEAN Trade Levels and ASEAN’s Average Trade Level. With this, the effect of the Philippine Total Trade, GDP by Sector, Foreign Direct Investment (FDI), and Intra-ASEAN Trade by Products on the Philippine Intra-ASEAN Trade Level were examined among the ASEAN-4 nations – Indonesia, Malaysia, Thailand, and Singapore. Such was necessary to state if a connection exists between the former and the latter. Moreover, as numerous countries form trade blocs globally, trade agreements for broader economic integration and grow their trade, as the world is interconnected through trade. This study will reinforce those external initiatives by foreign countries (FDI) and regional organizations (ASEAN) will remain keys to further trade liberalization and economic growth in the Philippines.